Efecto de una intervención educativa en la prevención y control de malaria en un área endémica de Loreto – 2025 - García Wong, Bettina Alessandra (2025)
Objective: To evaluate the effect of an educational intervention on the prevention and control of malaria in a population from an endemic area of Loreto, Peru, in 2025. Methods: A quantitative, quasi-experimental study was conducted in two localities: San Pablo de Cuyana (intervention group, 43 households) and Santa Rita del Nanay (control group, 60 households). The intervention included face-to face educational sessions using participatory strategies and illustrated materials aimed at strengthening malaria-related knowledge and promoting preventive practices. In both communities, a pre- and post-intervention survey was conducted to assess knowledge level, preventive practices, treatment adherence, and malaria incidence. Results: The educational intervention was implemented with active participation from 89% of the households in San Pablo de Cuyana. In this group, significant improvements were observed in knowledge levels in 48.8% of cases and in preventive practices in 37.2% of cases. In contrast, the control group showed minimal changes, with only 11.7% improvement in both knowledge and preventive practices. The differences between both groups were statistically significant (p < 0.05). The net improvement effect was +36.2 percentage points for knowledge and +32.9 for practices. The risk ratio indicated that the intervention group was 61% more likely to achieve a high level of knowledge and 43% more likely to adopt adequate preventive practices. Conclusion: The educational intervention had a positive impact on improving knowledge, preventive practices, and malaria control in the intervention group.